The Pleasure of Finding Things Out - Feynman,Richard P (Newyork : Basic Books, 1999)
The Pleasure of Finding Things Out is a magnificent treasury of the best short works of Richard P. Feynman-from interviews and speeches to lectures and printed articles. A sweeping, wide-ranging collection, it presents an intimate and fascinating view of a life in science-a life like no other. From his ruminations on science in our culture to his Nobel Prize acceptance speech, this book will fascinate anyone interested in the world of ideas.
Keywords: Biography; Physics -- Biography of a scientist